Phospholipase pPLAIIIα Increases Germination Rate and Resistance to Turnip Crinkle Virus when Overexpressed. Issue 3 (28th August 2020) - Jang, Jin Hoon; Nguyen, Ngoc Quy; Légeret, Bertrand; Beisson, Fred; Kim, Yu-Jin; Sim, Hee-Jung; Lee, Ok Ran
Abstract : Overexpression of a patatin-related phospholipase in Arabidopsis increases seed germination rate and confers turnip crinkle virus resistance. Abstract: Patatin-related phospholipase As (pPLAs) are major hydrolases acting on acyl-lipids and play important roles in various plant developmental processes. pPLAIII group members, which lack a canonical catalytic Ser motif, have been less studied than other pPLAs. We report here the characterization of pPLAIIIα in Arabidopsis ( Arabidopsis thaliana ) based on the biochemical and physiological characterization of pPLAIIIα knockouts, complementants, and overexpressors, as well as heterologous expression of the protein. In vitro activity assays on the purified recombinant protein showed that despite lack of canonical phospholipase motifs, pPLAIIIα had a phospholipase A activity on a wide variety of phospholipids. Overexpression of pPLAIIIα in Arabidopsis resulted in a decrease in many lipid molecular species, but the composition in major lipid classes was not affected. Fluorescence tagging indicated that pPLAIIIα localizes to the plasma membrane. Although Arabidopsis pplaIIIα knockout mutants showed some phenotypes comparable to other pPLAIIIs, such as reduced trichome length and increased hypocotyl length, control of seed size and germination were identified as distinctive pPLAIIIα -mediated functions. Expression of some PLD genes was strongly reduced in the pplaIIIα mutants. Overexpression of pPLAIIIα caused increased resistance to turnip crinkle virus, which associated with a 2-fold higher salicylic acid/jasmonic acid ratio and an increased expression of the defense gene pathogenesis-related protein1. These results therefore show that pPLAIIIα has functions that overlap with those of other pPLAIIIs but also distinctive functions, such as the control of seed germination. This study also provides new insights into the pathways downstream of pPLAIIIα .